2002
DOI: 10.1038/ng932
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan for familial nasopharyngeal carcinoma reveals evidence of linkage to chromosome 4

Abstract: Nasopharyngeal carcinoma (NPC) occurs with high frequency in Asian populations, especially among people of Cantonese ancestry. In areas with high incidence, NPC clusters in families, which suggests that both geography and genetics may influence disease risk. Although the HLA-Bw46 locus is associated with increased risk of NPC, no predisposing genes have been identified so far. Here we report the results of a genome-wide search carried out in families at high risk of NPC from Guangdong Province, China. Parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
151
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(152 citation statements)
references
References 17 publications
1
151
0
Order By: Relevance
“…These haplotypes include HLA A2-B46, HLA B17, HLA A2-B38, and HLA A2-B16 [24,25]. The genetic bases of familial NPC are not well understood, but susceptibility loci have been identified in chromosome regions 3p21 and 4p15 [26,27].…”
Section: Genetic Riskmentioning
confidence: 99%
“…These haplotypes include HLA A2-B46, HLA B17, HLA A2-B38, and HLA A2-B16 [24,25]. The genetic bases of familial NPC are not well understood, but susceptibility loci have been identified in chromosome regions 3p21 and 4p15 [26,27].…”
Section: Genetic Riskmentioning
confidence: 99%
“…Several factors have been identified in its aetiology in recent years, including infection of the Epstein-Barr virus (EBV), environmental risk factors and genetic susceptibility [1,2,5]. Of these aetiological factors, EBV infection appears to be the most important one [1][2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular basis of NPC development is still poorly elucidated, NPC pathogenesis has been shown to be strongly associated with Epstein-Barr virus (EBV), whether endemic or sporadic (Pathmanathan et al, 1995;Raab-Traub 2002). Consumption of salted fish in early childhood, tobacco smoking (Yu and Yuan 2002) and genetic predisposition (Lu et al, 1990;Feng et al, 2002;Xiong et al, 2004) have also been suggested as risk factors.…”
mentioning
confidence: 99%